Triticum aestivum L. subsp. aestivum CWI 7066 ... - GLIS Of The ITPGRFA (Centro Internacional de Mejoramiento de Maíz y Trigo, 2017)
Plant Genetic Resource. Taxonomy: Triticum aestivum L. subsp. aestivum Common name(s): Wheat Other names: SAKHALIN LUTESCES 34 Conserved by: Centro Internacional de Mejoramiento de Maíz y Trigo (CIMMYT), Mexico Local sample unique identifier: CWI 7066 Method of creation: Acquisition Date: 1988 Other identifiers: n/a,CWI7066, n/a,PI 182530, n/a,GID 286594, n/a,CID 271171 SID 0 Historical: No Biological status: Breeder's line MLS status: Included ...